Competences of gratuate from grammar schools in Basics of Civics Social Science - Vaníčková, Vanda (Civilia, 2014)
School Educational Programms are tool for schools to make their own vision by general programme of education. This contribution will target on key competences, which School Education Programms of chosen schools describe for subject Basics of Civics Social Science. The aim of contribution is analyze focus of competences, classified them and name requirements on teachers of Basics of Civics Social Science.
Keywords: Key competences; Basics of Civics Social Science; Grammar schools; School Education Programme